Cellular Organization and Cytoskeletal Regulation of the Hippo Signaling Network. Issue 9 (September 2016) - Sun, Shuguo; Irvine, Kenneth D.
Abstract : The Hippo signaling network integrates diverse upstream signals to control cell fate decisions and regulate organ growth. Recent studies have provided new insights into the cellular organization of Hippo signaling, its relationship to cell–cell junctions, and how the cytoskeleton modulates Hippo signaling. Cell–cell junctions serve as platforms for Hippo signaling by localizing scaffolding proteins that interact with core components of the pathway. Interactions of Hippo pathway components with cell–cell junctions and the cytoskeleton also suggest potential mechanisms for the regulation of the pathway by cell contact and cell polarity. As our understanding of the complexity of Hippo signaling increases, a future challenge will be to understand how the diverse inputs into the pathway are integrated and to define their respective contributions in vivo . Trends: Hippo signaling is a complex network that integrates multiple growth-control signals through an expanding set of core kinases. Recent studies have provided insights into the cellular organization of Hippo signaling, including where pathway components localize, where key events occur inside the cell, and how changes in protein localization modulate pathway activity. Scaffolds play an essential role in Hippo signal transduction by assembling kinase activation complexes through their ability to bind multiple pathway components. Localization of these scaffolds to cell junctions provides a basis for the sensitivity of Hippo signaling to cell contact and cell polarity. Progress has been made in identifying mechanisms by which the cytoskeleton and mechanical forces can regulate Hippo signaling.